2017
DOI: 10.1515/cer-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Personal Finances vs. the Overall Economic Conditions: What Drives the New EU Member States’ Stock Markets?

Abstract: This paper analyses the leading characteristics of the Consumer Confidence Index (CCI) with respect to stock market returns for 11 New EU Member States. It proposes novel CCI weights by minimizing mean squared errors from regression forecasting equations, using CCI lags as regressors. With regards to the obtained “optimal” weights, the examined countries are grouped into micro‑ and macro‑oriented clusters. A strong shift is found in the weights due to the recent recession. The micro aspects (reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Another related example is Lolić et al (2017), who have shown that the macroeconomic sentiment of the evolution of the national economy-a crucial psychological dimension of consumer confidence-grows significantly during a macroeconomic crisis. Relatedly, Giugni and Mexi (2018) have observed that even if the 2008 recession had few measurable macroeconomic effects on Switzerland's economy, its citizens still experienced its deleterious effects in terms of negative perceptions of economic conditions.…”
Section: Perceptions Of Economic Conditions and Subjective Well-beingmentioning
confidence: 99%
“…Another related example is Lolić et al (2017), who have shown that the macroeconomic sentiment of the evolution of the national economy-a crucial psychological dimension of consumer confidence-grows significantly during a macroeconomic crisis. Relatedly, Giugni and Mexi (2018) have observed that even if the 2008 recession had few measurable macroeconomic effects on Switzerland's economy, its citizens still experienced its deleterious effects in terms of negative perceptions of economic conditions.…”
Section: Perceptions Of Economic Conditions and Subjective Well-beingmentioning
confidence: 99%